2000
DOI: 10.1093/carcin/21.5.391
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic rats carrying copies of the human c-Ha-ras proto-oncogene exhibit enhanced susceptibility to N-butyl-N-(4-hydroxybutyl)nitrosamine bladder carcinogenesis

Abstract: We have established a transgenic rat line carrying three copies of the human c-Ha-ras proto-oncogene with its own original promoter region, Jcl/SD-TgN(HrasGen)128Ncc (Hras128) rat. c-Ha-ras protein from expression of transduced and endogenous c-Ha-ras genes could be detected in the bladder epithelium of untreated transgenic rats. To examine their susceptibility to N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN)-induced urinary bladder carcinogenesis, male transgenic and wild-type littermates were treated with 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Taken together with the fact that activating mutations in Hras are an early event in the development of a subset of human UC, this suggests that mutation of the Hras transgene is a primary factor in the development of invasive UC in the animal model described in this study. However, it has been demonstrated that enhanced UC development is not primarily due to mutations occurring in the transgene in Hras128 rats . Another factor in the susceptibility of Hras128 to UC could be relatively high expression of the human Hras transgene.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with the fact that activating mutations in Hras are an early event in the development of a subset of human UC, this suggests that mutation of the Hras transgene is a primary factor in the development of invasive UC in the animal model described in this study. However, it has been demonstrated that enhanced UC development is not primarily due to mutations occurring in the transgene in Hras128 rats . Another factor in the susceptibility of Hras128 to UC could be relatively high expression of the human Hras transgene.…”
Section: Discussionmentioning
confidence: 99%
“…9) Similarly, transgenic rats carrying a probesin promoter fused to the SV 40 T antigen gene have been shown to develop prostatic tumors. 10,11) In addition, we have generated transgenic rats utilizing the same gene construct employed for generation of human c-Ha-ras proto-oncogene transgenic mice 12) and shown them to be highly susceptible to induction of tumors in the mammary tissue by N-methyl-N-nitrosourea (MNU) and 7,12dimethylbenz[a]anthracene (DBMA), 12,13) in the urinary bladder by N-butyl-N-(4-hydroxybutyl)nitrosamine 14) and in the esophagus by N-nitrosomethylbenzylamine. 15) The model has also proven to be useful for demonstrating effects of inhibitory potential in the mammary gland.…”
mentioning
confidence: 99%
“…7) In humans, Ki-ras mutations are preferentially found in colon, 8,9) pancreatic duct 10) and bile duct carcinomas, 11) and N-ras mutations are typically seen in myeloid leukemia. 12) We have generated a transgenic rat line, harboring copies of a human c-Ha-ras proto-oncogene (Hras128 rat), and have shown that these animals are highly susceptible to mammary, 13,14) bladder 15) and esophageal 16) carcinogens.…”
mentioning
confidence: 99%